Sentence comprehension in Parkinson's disease - Fernanda Prieto; Márcia Radanovic; Cristina Schmitt; Egberto Reis Barbosa; Letícia Lessa Mansur (Dementia & Neuropsychologia)
Abstract Parkinson's disease (PD) patients with dementia have impairment of syntactic comprehension. Non-demented PD patients also experience difficulties in sentence comprehension and can be particularly impaired in the processing of grammatical characteristics of syntactically complex sentences. Objective: The aim of this study was to verify the performance of PD patients without dementia in a syntactic comprehension task compared with normal elderly. Methods: We studied oral sentence comprehension in fourteen patients with idiopathic PD together with fourteen controls matched for age and education, using the Token Test and Schmitt's Syntactic Comprehension Test (developed in Brazilian Portuguese). Results: For the Token Test, there was no statistically significant difference between the PD group and the control group, whereas on the Syntactic Comprehension Test there was a slight statistically significant difference between the groups only for relatives in subject clauses (p=0.0407). Conclusions: PD patients differed from controls in the oral comprehension for relatives subject sentences alone. These results did not strictly reproduce those previously reported in the literature, and therefore point to the need for creating tests with diverse syntactic constructions in Portuguese able to produce consistent data regarding language behavior of Brazilian subjects with PD in comprehension tasks.